Hydrolytic Capabilities as a Key to Environmental Success: Chitinolytic and Cellulolytic Acidobacteria From Acidic Sub-arctic Soils and Boreal Peatlands - Belova, Svetlana E.; Ravin, Nikolai V.; Pankratov, Timofey A.; Rakitin, Andrey L.; Ivanova, Anastasia A.; Beletsky, Alexey V.; Mardanov, Andrey V.; Sinninghe Damsté, Jaap S.; Dedysh, Svetlana N. (Frontiers in Microbiology, 2018)
Members of the Acidobacteria are among the most efficient colonizers of acidic terrestrial habitats but the key traits underlying their environmental fitness remain to be understood. We analyzed indigenous assemblages of Acidobacteria in a lichen-covered acidic (pH 4.1) soil of forested tundra dominated by uncultivated members of subdivision 1. An isolate of these bacteria with cells occurring within saccular chambers, strain SBC82T, was obtained. The genome of strain SBC82T consists of a 7.11-Mb chromosome and four megaplasmids, and encodes a wide repertoire of enzymes involved in degradation of chitin, cellulose, and xylan. Among those, four secreted chitinases affiliated with the glycoside hydrolase family GH18 were identified. Strain SBC82T utilized amorphous chitin as a source of carbon and nitrogen; the respective enzyme activities were detected in tests with synthetic substrates. Chitinolytic capability was also confirmed for another phylogenetically related acidobacterium isolated from a Sphagnum peat bog, strain CCO287. As revealed by metatranscriptomic analysis of chitin-amended peat, 16S rRNA reads from these acidobacteria increased in response to chitin availability. Strains SBC82T and CCO287 were assigned to a novel genus and species, Acidisarcina polymorpha gen. nov., sp. nov. Members of this genus colonize acidic soils and peatlands and specialize in degrading complex polysaccharides.